Políticas públicas e abordagem das capacitações: uma análise do programa bolsa família a partir do censo 2010 - Azevedo, Vanessa Ragone (2017)
The Bolsa Família Program unified income transfer programs and facilitated control, oversight and provided the possibility of integration with other programs as stated Sanson (2008). Weissheimer (2006) stresses that the improvements were not only to rationalize and expand existing programs, not limited to the greater transfer of income, but also to the repercussions of the school attendance requirement of the children of beneficiary families, compliance with the vaccination schedule and follow-up of gestation and prohibition of Child labor. Based on the understanding that a policy to combat poverty must act in areas other than income transfer, Amartya Sen's theory allows a better basis for analyzing these effects and needs. The capabilities approach developed by Sen (1999) considers that the expansion of personal skills should be the goal of the development process and not the expansion of wealth or income, wealth should be seen as a means and not as an end of the process. In this dissertation, the policy analyzed was the Bolsa Família Program, using the theoretical basis of the training approach, 18 variables were distributed among four dimensions: housing, work, education and health. At the end of the analysis of all dimensions, the best gross results were found, for the majority of the variables, in the southeast region, mainly São Paulo State, indicating that this region has more infrastructure compared to the other regions of the country; Among the worst results, the northern region had the worst gross results, especially in variables related to access to durable goods and local infrastructure (sewerage, general grid, energy). The comparative result that indicates the local deprivation of the beneficiaries in the north and northeast region was positive, since it presented smaller differences between beneficiaries and non beneficiaries. Another important result was that variables such as: bathroom, refrigerator, no portfolio, no education, Micropc, sewage and garbage, control of observable characteristics was not enough to explain the difference between groups, with positive results concentrated in non-beneficiaries; Already for the variables: busy, job search, working hours and general network had the difference explained in great part by the characteristics, with approximation of the results between groups after the pairing. For the variables that have conditionality directly linked to the PBF, the results were expressively higher among the beneficiaries, indicating that this counterpart method is efficient; The results indicated that the beneficiaries of the program have deficiencies in all dimensions, with difficulties of access to basic housing, work, education and health conditions that in some part could be explained by the observable characteristics, demonstrating that this deficiency is related to the geographic region And income, color, age and sex, in other variables, beneficiaries have less access even compared to individuals with similar characteristics. As the PBF is applied without distinction in all regions of the country, it has bottlenecks that can be improved by observing local needs and infrastructure and access difficulties in each region, allowing a broadening of benefits beyond conditionalities.